Common Property Wasteland-Use Planning for Sustainable Resource Development in Ramgad Catchment, Kumaun Himalaya - Vigra, CS; Jina, BS; Sah, P; Bhatt, MD (Scientific World, 2010)
The Lesser Himalayan region is the most densely populated area of all the Himalayan ranges and deserves specific and adequate attention for the development of its scarce and precious common property wasteland resource in view of the fact that a large number of rural poor households in the region depend on common property wastelands for the fulfillment of their own basic needs, such as, fodder, fuel-wood, grazing etc. Of late, the region is experiencing extensive environmental problems like deforestation, landslides, soil erosion, owing mainly to the over-utilization of common property resources. This is consequent to the misuse and mismanagement of the common property land resources by villagers in Himalayan region. This paper attempts to evolve an optimal wasteland use framework for the Ramgad catchment situated in the Lesser Himalayan ranges of district Nainital located in the Himalayan state of Uttarakhand. Recognizing the drastic changes that have taken place in traditional common property wasteland use, the watershed area has been proposed to be marked for fodder development, horticultural development and medicinal plant conservation. Key words: Wasteland; Natural resource; Households; Kumaun Himalayas. DOI: 10.3126/sw.v7i7.3823 Scientific World Vol.7(7) 2009 pp.41-46